Assessment of solar driven TiO2-assisted photocatalysis efficiency on amoxicillin degradation - João H. O. S. Pereira (2014)
The objective of this work was to evaluate the efficiency of a solar TiO2-assisted photocatalytic process on amoxicillin (AMX) degradation, an antibiotic widely used in human and veterinary medicine. Firstly, solar photolysis of AMX was compared with solar photocatalysis in a compound parabolic collectors pilot scale photoreactor to assess the amount of accumulated UV energy in the system (Q (UV)) necessary to remove 20 mg L-1 AMX from aqueous solution and mineralize the intermediary by-products. Another experiment was also carried out to accurately follow the antibacterial activity against Escherichia coli DSM 1103 and Staphylococcus aureus DSM 1104 and mineralization of AMX by tracing the contents of dissolved organic carbon (DOC), low molecular weight carboxylate anions, and inorganic anions. Finally, the influence of individual inorganic ions on AMX photocatalytic degradation efficiency and the involvement of some reactive oxygen species were also assessed. Photolysis was shown to be completely ineffective, while only 3.1 kJ(UV) L-1 was sufficient to fully degrade 20 mg L-1 AMX and remove 61 % of initial DOC content in the presence of the photocatalyst and sunlight. In the experiment with an initial AMX concentration of 40 mg L-1, antibacterial activity of the solution was considerably reduced after elimination of AMX to levels below the respective detection limit. After 11.7 kJ(UV) L-1, DOC decreased by 71 %; 30 % of the AMX nitrogen was converted into ammonium and all sulfur compounds were converted into sulfate. A large percentage of the remaining DOC was in the form of low molecular weight carboxylic acids. Presence of phosphate ions promoted the removal of AMX from solution, while no sizeable effects on the kinetics were found for other inorganic ions. Although the AMX degradation was mainly attributed to hydroxyl radicals, singlet oxygen also plays an important role in AMX self-photosensitization under UV/visible solar light.